Implementing Mconf web conferencing at the South African National Research and Education Network - Isaac, Kasandra (My University, 2015)
Mconf web conferencing has been launched successfully as a South African National Research and Education Network (SA NREN) production level service from July 2015. This web conferencing service is an Open Source Multi-conference System funded mainly by the Brazilian National Research and Education Network (NREN), Rede Nacional de Ensino e Pesquisa (RNP). Mconf is a research collaboration tool that is web based and that can also be set up as a room based video conferencing system. It can be used for distance education, remote meetings or broadcasting of events and offers a range of collaboration tools such as a whiteboard, document repositories, collaboration spaces, shared notes and more. The service has been integrated with the South African Federated Identities for Research and Education (SAFIRE) to allow users to be able to access the service quickly and easily using their home institutions credentials. By integrating Mconf web conferencing with SAFIRE, the SA NREN hopes that Mconf will encourage institutions that are not registered to SAFIRE to join the federation.
Keywords: Global Web conferencing Network; Video conference; Web conference; Collaboration; Communication; Federated Identity; Value-added service